O lúdico como instrumento facilitador para o ensino nas turmas da educação infantil da escola do campo - FARIAS, Ramon Pantoja (2023)
He ludic in addition to a school content is a way that the teacher has to mediate the relationship between knowledge and students, providing an easier and more pleasant learning. This work is the result of a research that sought to identify how play has been used as a pedagogical tool in teaching work in early childhood education classes, having as an investigative focus the Nossa Senhora do Perpétuo school, located in a riverside community in Abaetetuba-Pará. The research was theoretically based on Kishimoto (2011); Venturini (2016); Sommerhalder and Alves (2011); Klassmann (2013); Rocha (2014); between others. In the course of the research, it became necessary, in addition to the theoretical investigation, to carry out fieldwork in the riverside location where the school is located, making it possible to carry out a direct observation in a kindergarten classroom. The analyzes have as their main basis the work of teachers, the theoretical contextualization and the way in which the management subsidizes the work within the schools, emphasizing broadly the context that each student is inserted. Obtaining as a result the application of didactic actions consistent with the theoretical basis discussed, the ludic activities presented at the end of the research reflect the need to include games in the school routine to facilitate the learning process.